1982
DOI: 10.4141/cjas82-129
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian and Estrous Activity Throughout the Year in Pregnant and Nonpregnant Ewes Selected for Extended Breeding Season

Abstract: Twenty-nine DLS (l/2 Dorset, 1/4 Leicester, 1/4 Suffolk) ewes selected for extended breeding season, were involved in this study which lasted for 18 mo. According to their lambing date relative to January first, 15 ewes had a high lambing index whereas the others had a low index, the difference being 33 days (P<0.01). Half the ewes were assigned at random to remain nonpregnant throughout the study, whereas the other half was mated in July and August. From I May to 15 July, 20 ewes (69%') were cycling of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

1985
1985
2000
2000

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
1
3
1
Order By: Relevance
“…In the present study, and in those of Hulet et al (1914) and Dufour et al (1982), the sexual activity of the ewes during the summer following a long trip were different from that of the succeeding summer' In this study most of the ewes developed follicles Can. J. Anim.…”
Section: The Comparable Estimate Reported Bycontrasting
confidence: 52%
See 1 more Smart Citation
“…In the present study, and in those of Hulet et al (1914) and Dufour et al (1982), the sexual activity of the ewes during the summer following a long trip were different from that of the succeeding summer' In this study most of the ewes developed follicles Can. J. Anim.…”
Section: The Comparable Estimate Reported Bycontrasting
confidence: 52%
“…The present data suggest that the extension of the breeding season in this sample took place toward the end rather than at the beginning, since the two breeding seasons began almost a month later than that of 28 July reported earlier by Dufour (1914) and Dufour et al (1982) for two earlier studies on the DLS population' Since lambing in the preceding season interferes with the resumption of ovarian activity, many ewes would not benefit from this extended breeding activity towards the end of their season. Ewes which lamb and wean early may have a chance of resuming cycling activities before starting their anestrous period (Dufour et al 1982).…”
Section: The Comparable Estimate Reported Bysupporting
confidence: 39%
“…No breed groups had more than 50% of ewes cycling in June or July. Dufour et al (1982) reported that a composite breed (DLS: ¹⁄₂ Dorset, ¹⁄₄ Leicester, ¹⁄₄ Suffolk) had a longer breeding season than any of the component purebreds. The DLS ewes began cycling Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…Patterns of estrous behavior were reported to be highly repeatable across years, and two ewes cycled continuously for the entire 4-yr period. Dufour et al (1982) reported that two of 29 DLS ewes cycled continuously from May 1 through the summer, but both had stopped cycling by April of the next year.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have been reported on the characteristics of occurrence of first oestrus in sheep but there is some evidence as in this study that the trait is heritable (Dufour, Fahmy, Adelakoun, and Matton, 1982). Few studies have been reported on the characteristics of occurrence of first oestrus in sheep but there is some evidence as in this study that the trait is heritable (Dufour, Fahmy, Adelakoun, and Matton, 1982).…”
Section: The Heritability Values Inmentioning
confidence: 53%